Alimentación de pollos de engorde con residuos de panadería en la Universidad Técnica de Cotopaxi Campus Salache en la Facultad de Ciencias Agropecuarias y Recursos Naturales - Calero Ortiz, Edison Ivan (2019)
The present investigation was carried out in Salache campus at Cotopaxi Technical University, to determine the effects of different levels of bakery residues (RP) in fattening chickens in front of a witness fed with commercial balanced, and its influence in the zoo technical parameters, productive and economical for 7 weeks. 100 fattening chickens were used, divided into four treatments (T0%, T5%, T10% and T15%) with 5 repetitions each and a U.E size of 5. The design of the experiment was DCA. We begin the reception with weighing and differentiated feeding of the birds; the supply of food and weighing of daily waste and record of weight of the birds and weekly costs. We carried out the ADEVA and concluded that there are highly significant differences in weight (P), weight gain (GP) and food consumption (COA) of the different treatments, with the best results being T0% and T15%. On the other hand, the indicators of food conversion (CA), food efficiency index (IEA) and productivity index (PI) registered high significance differences (<0.001) in week 1, 4 and 7; but were statistically equal in weeks 2,4,5; considering that their values are within the recommended parameters for the conditions and altitudinal floor of the area. As for the cost per kilogram of weight gain of the bird, marked statistical differences were obtained, being the best in all the weekly stages the T15%. The economic benefit / cost analysis (B / C) was favorable for the treatment with 15% of bakery waste since the feeding cost was lower than the control treatment (T0%), reporting a B / C of 1.20 and 1,15 respectively.